2019
DOI: 10.1002/eat.23051
|View full text |Cite
|
Sign up to set email alerts
|

Increased lipid and lipoprotein concentrations in anorexia nervosa: A systematic review and meta‐analysis

Abstract: Objective: Alterations in blood lipid concentrations in anorexia nervosa (AN) have been reported; however, the extent, mechanism, and normalization with weight restoration remain unknown. We conducted a systematic review and a meta-analysis to evaluate changes in lipid concentrations in acutely-ill AN patients compared with healthy controls (HC) and to examine the effect of partial weight restoration. Method: A systematic literature review and meta-analysis (PROSPERO: CRD42017078014) were conducted for origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 75 publications
(148 reference statements)
4
31
1
2
Order By: Relevance
“…The data extraction sheet was based on two previous meta‐analyses (Hussain et al, ; Ilyas et al, ) and included variables that were hypothesized to be associated with body composition, hormonal, or metabolic measures, including fasting status and period, medications, stage of the menstrual cycle, or treatments for longitudinal studies. If enough studies reported these variables, we performed meta‐regressions to investigate their associations with our primary and secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data extraction sheet was based on two previous meta‐analyses (Hussain et al, ; Ilyas et al, ) and included variables that were hypothesized to be associated with body composition, hormonal, or metabolic measures, including fasting status and period, medications, stage of the menstrual cycle, or treatments for longitudinal studies. If enough studies reported these variables, we performed meta‐regressions to investigate their associations with our primary and secondary outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Anorexia nervosa (AN) has one of the highest mortality rates of all psychiatric disorders (Chesney, Goodwin, & Fazel, ). Clinical observations show altered body composition (El Ghoch, Calugi, Lamburghini, & Dalle Grave, ; Solmi et al, ) accompanied by elevated cholesterol (Hussain et al, ) and greater insulin sensitivity (Ilyas et al, ). However, conclusions are limited by small sample sizes and consequent mixed findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very low-density lipoproteins transport endogenous produced lipids from the liver to peripheral tissues. A meta-analysis observed no association between very low-density lipoprotein and anorexia nervosa in acutely ill patients [14]. However, only three studies with 90 anorexia nervosa cases were included to obtain the pooled estimate and heterogeneity was high.…”
Section: Discussionmentioning
confidence: 99%
“…Нервная анорексия. В одном из систематических обзоров и мета-анализе литературы были проиллюстрированы изменения липидного профиля у пациентов с нервной анорексией в виде повышения концентрации ОХ, ЛВП, ЛНП и триглицеридов [12]. Предполагают, что при нервной анорексии может развиваться повышенное всасывание жиров кишечником вследствие изменений в микробиоте, о чем свидетельствуют более высокие концентрации фитостеролов, в частности кампестерола и бета-ситостерола, у пациентов с нервной анорексией [13].…”
unclassified